Invitation to tender / Izhar Hairee Zawawi - Zawawi, Izhar Hairee (Universiti Teknologi MARA, Perak, 2018)
An invitation to tender is a formal invitation to make an offer for the supply of goods or services. The main topic discussed in this report is related to the tender submission of a construction project based on the project Structure for KPJ Ampang Puteri Specialist Hospital at Jalan Selaman 1, Ampang, Selangor Darul Ehsan. This report describes the method to make an invitation to tender. It also determines what is needed to put in an invitation to tender. Observation and interviews with related individuals were required to complete this report. In conclusion this report includes the requirements for an invitation to tender and the process of an invitation to tender which are the elements related to the invitation to tender.